Organic pollutants in water samples of Vjosa river: Albania - Aurel Nuro; Elda Marku; Bledar Murtaj (Zaštita Materijala)
The findings reported here belong to a study on determination of organochlorine pesticides, their residues, polychlorinated biphenyls, polyaromatic hydrocarbons and BTEX concentrations in water samples of Vjosa River (Albanian part). The Vjosa River in Albania is one of Europe's last living wild rivers. Water samples were taken in 12 stations starting from Sarandoporo (Leskovik, Kolonje) to Vjosa river mouth (Adriatic Sea), in March 2017. Organochlorine compounds and PCB markers were extracted using liquid-liquid technique using n-hexane as extracting solvent. PAHs were extracted also using liquid-liquid technique using dichloromethane as extracting solvent. After extraction the organic phase was dried with Na2SO4 anhidrous, for removing water. A Florisil column was used for the sample clean-up. After the concentration to 1 ml, the samples were injected in Varian 450 GC equiped with ECD and FID detectors. BTEX were extracted using HS/SME technique with PDMS fiber. Found data shown persistent levels of pesticides and their metabolites in water samples because their previous use. PCBs, PAHs and BTEX were found also for all samples. Their presence could be because of anthropogenic and automobilist impact in waters of Vjosa River. The found levels for organic pollutants in waters of Vjosa River were lower than reported levels for other ecosystems in Alb ania.